Determining the Relationship between Blood Donation and Altruism Level - Arzu Önel; Meryem Konu-Kadirhanoğullari; Şule Firat-Durdukoca (International Journal of Contemporary Educational Research)
Altruism means helping others without expecting anything in return and solely for the sake of others; Blood donation is one of the best examples of this pure aid. This research aims to examine the relationship between teacher candidates' altruism levels and blood donation attitude levels. The relational screening method, one of the subcategories of the general screening model, was used in the research. The research was conducted with 204 teacher candidates studying at a state university in Turkey. Data were collected from the “Blood Donation Attitude Scale” developed by Çelik & Güven (2015); It was obtained by using the "Altruism Attitude Scale" developed by Ümmet, Ekşi & Otrar (2013) and the questions prepared by the researchers by taking advantage of the literature and taking expert opinions. Frequency and percentage calculations, mean, standard deviation and Pearson correlation analysis were used to evaluate the data. As a result of the research, it was determined that there was a significant and statistically moderate positive relationship between the level of altruism and blood donation attitude. It was determined that the "Social and Social Responsibility" factor had the highest mean value for the Blood Donation Attitude Scale sub-dimensions, and the "Help in Traumatic Situations" factor had the highest mean value for the Altruism Attitude Scale sub-dimensions.